Determinant factors of sedentary time in individuals with COPD - Tofoli, Thais Moçatto; Santin, Laís; Medeiros, Letícia; Silva, Humberto; Garcia, Isabella Ortiz; Camillo, Carlos Augusto [UNESP]; Furlanetto, Karina Couto; Hernandes, Nidia Aparecida; Pitta, Fabio (Elsevier, 2024)
Background: The factors influencing sedentary time (ST) of individuals with chronic obstructive pulmonary disease (COPD) have not been thoroughly explored. Aim: To identify determinant factors of ST in individuals with stable COPD. Methods: Individuals with COPD had their ST and variables of physical activity (PA) cross-sectionally assessed during seven days with an activity monitor. Main variables were ST/day (<1.5 METs), steps/day, time/day in light PA (light PA/day, 1.5–2.9 METs) and in moderate-to-vigorous PA (MVPA/day, ≥3 METs). Additional assessments included 6-min walking test (6MWT), Medical Research Council (MRC) scale, lung function and body composition. Multiple linear regression models were built with variables correlating significantly with ST/day. Results: 50 individuals were analyzed (44 % males; 66 ± 8 years; FEV1 50 ± 19%pred). ST/day was 488 ± 160 min (61 ± 15 % of the day). 6MWT, MRC scale, MVPA/day, steps/day and light PA/day correlated significantly with ST expressed as minutes/day or as % of the day. In the multiple regression analyses, variables explaining the variance of ST in minutes/day were MRC scale (1 %) and light PA/day (53 %) (model R2 = .541, p < 0.001) and of ST in % of the day were steps/day (53 %) and light PA/day (46 %) (model R2 = .994, p < 0.001). Conclusion: In individuals with COPD, the variance in sedentary time can be explained by dyspnea in daily life, step count and specially time/day in light PA, which reinforces the increase in light PA (rather than necessarily MVPA) as a strategy to reduce sedentary time.
Keywords: Chronic obstructive pulmonary disease; Physical activity; Sedentary behavior